PENGARUH SENAM HAMIL TERHADAP PENURUNAN NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER II DAN III DI KECAMATAN PANEI TAHUN 2021 - Netty Julita Siahaan; Adelina Sembiring; Retno Wahyuni (Pusat riset dan Inovasi Nasional, 2022)
Low back pain during pregnancy occurs due to changes in pregnancy hormones which increase relaxant hormones that affect the flexibility of the ligament tissue which ultimately increases joint mobility in the pelvis and will have an impact on spinal and pelvic instability and cause back pain. One way to reduce low back pain is to do pregnancy exercises. Pregnancy exercise can relieve lower back pain that is felt by pregnant women because in pregnancy exercise there are movements that can strengthen the abdominal muscles, make the elasticity of the muscles and ligaments in the back and relax, so that pregnant exercise can reduce lower back pain. The purpose of this study was to determine the effect of pregnancy exercise on reducing low back pain in pregnant women in the second and third trimesters in Panei District 2021. This study used a quasi-experimental research design with a pre-post-test design with one group test. The population in this study were all pregnant women in the second and third trimesters in Panei Tongah Health Center many as 30 people. The sample in this study amounted to 28 people. Analysis of the data used is univariate analysis and bivariate analysis using the Paired-Samples T Test. The average lower back pain before treatment was 3.32 and the Std. Deviation was 0.772. The average low back pain after treatment was 2.25 and the Std. Deviation was 1.005. There is an effect of pregnancy exercise on reducing low back pain in pregnant women in the second and third trimesters in Panei Tongah Health Center in 2021 with a value of p = 0.000 p <0.05. It is recommended for further researchers to develop other variables in order to get better results Panei Tongah Health Center.